Repurposing of Anti-Diabetic Agents as a New Opportunity to Alleviate Cognitive Impairment in Neurodegenerative and Neuropsychiatric Disorders - Chen, Qian; Cao, Ting; Li, NaNa; Zeng, Cuirong; Zhang, Shuangyang; Wu, Xiangxin; Zhang, Bikui; Cai, Hualin (Frontiers in Pharmacology, 2021)
Cognitive impairment is a shared abnormality between type 2 diabetes mellitus (T2DM) and many neuropsychiatric disorders, such as schizophrenia and Alzheimer’s disease (AD). Emerging evidence suggests that brain insulin resistance plays a significant role in cognitive deficits, which provides the possibility of anti-diabetic agents repositioning to alleviate cognitive deficits. Both preclinical and clinical studies have evaluated the potential cognitive enhancement effects of anti-diabetic agents targeting the insulin pathway. Re-purposing of anti-diabetic agents is considered to be promising for cognitive deficits prevention or control in these neuropsychiatric disorders. This article reviewed the possible relationship between brain insulin resistance and cognitive deficits. In addition, promising therapeutic interventions, especially current advances in anti-diabetic agents targeting the insulin pathway to alleviate cognitive impairment in T2DM, AD and schizophrenia were also summarized.